1994
DOI: 10.1073/pnas.91.11.4930
|View full text |Cite
|
Sign up to set email alerts
|

Fas and its ligand in a general mechanism of T-cell-mediated cytotoxicity.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
115
0
3

Year Published

1996
1996
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(120 citation statements)
references
References 43 publications
2
115
0
3
Order By: Relevance
“…hFasL cDNA was prepared by reverse transcriptase-polymerase chain reaction (RT-PCR) from total RNA of activated human T cell clone (4HM1), transferred into the BCMGSneo expression vector, 19 and introduced into a murine T lymphoma cell line (L5178Y) which does not express Fas. 10,17,20 At the same time, we used control mock transfectants (mock/L5178Y), prepared by transferring empty vector alone into L5178Y. 17 Flow cytometry analysis showed that hFasL transfectants expressed a high level of hFasL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hFasL cDNA was prepared by reverse transcriptase-polymerase chain reaction (RT-PCR) from total RNA of activated human T cell clone (4HM1), transferred into the BCMGSneo expression vector, 19 and introduced into a murine T lymphoma cell line (L5178Y) which does not express Fas. 10,17,20 At the same time, we used control mock transfectants (mock/L5178Y), prepared by transferring empty vector alone into L5178Y. 17 Flow cytometry analysis showed that hFasL transfectants expressed a high level of hFasL.…”
Section: Resultsmentioning
confidence: 99%
“…9 This molecule is expressed on activated T cells and natural killer (NK) cells and induces apoptotic cell death in target cells expressing functional Fas antigen. [10][11][12] We previously established mice carrying human T cell leukemia virus type 1 (HTLV-1) representing one of the most suitable animal models of human RA. 13 Using this model, we have recently demonstrated that intra-articular administration of anti-Fas MAb improved the paw swelling and histological features of arthritis by induction of apoptosis of both synoviocytes and mononuclear cells in the inflamed synovium.…”
Section: Introductionmentioning
confidence: 99%
“…Fas is expressed on a variety of different cell types (8), though the physiological role of its wide constitutive expression has not yet been clarified. In contrast, FasL is more restricted in its expression and is inducibly expressed on T, B, and NK cells during activation of the immune system (9,10). Sequentially, Fas/FasL interaction down-regulates the immune response by inducing apoptosis, as activated lymphocytes express both Fas and FasL (11,12).…”
mentioning
confidence: 99%
“…Sequentially, Fas/FasL interaction down-regulates the immune response by inducing apoptosis, as activated lymphocytes express both Fas and FasL (11,12). The fact that dysregulation of the Fas system leads to uncontrolled lymphoproliferation and severe autoimmune disorders (13,14) means that the Fas system plays a role in the control of immune reactions in several organs in physiological and pathological conditions (9,15,16).…”
mentioning
confidence: 99%
“…One possibility is a soluble chimeric Fas-Ig fusion. 141 Indeed, data from a study where Fas-mediated cytotoxic activity by a T cell clone against sensitized recipient target cells could be prevented by addition of the Fas-Ig fusion protein, suggest that a local, high level transfer of the Fas-Ig cDNA to allografts may be feasible in preventing FasL-dependent destruction. Alternatively, signaling-defective, dominantnegative variants of Fas, mutant downstream effectors such as FADD (Fas-associated death domain protein)-a docking protein involved in linking the intracytoplasmic domain of Fas to the death effector molecules, 142,143 inhibitors of the proapoptotic cascade like crmA protein encoded by cowpox, 144 and bcl-2 family members [145][146][147][148][149][150] may all be useful in suppressing Fas-triggered apoptosis induction (Table 3).…”
Section: Inhibition Of Apoptosismentioning
confidence: 99%